2021
DOI: 10.48550/arxiv.2109.01051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can Error Mitigation Improve Trainability of Noisy Variational Quantum Algorithms?

Abstract: Variational Quantum Algorithms (VQAs) are widely viewed as the best hope for near-term quantum advantage. However, recent studies have shown that noise can severely limit the trainability of VQAs, e.g., by exponentially flattening the cost landscape and suppressing the magnitudes of cost gradients. Error Mitigation (EM) shows promise in reducing the impact of noise on near-term devices. Thus, it is natural to ask whether EM can improve the trainability of VQAs. In this work, we first show that, for a broad cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 96 publications
1
35
0
Order By: Relevance
“…Our framework -suitably extended -could thus identify new performance bounds in each of these settings. Note added.-During the completion of our manuscript, we became aware of an independent work by Wang et al [62], which showed a result related to our Theorem 5 on the exponential scaling of required samples in variational algorithms.…”
Section: Discussionmentioning
confidence: 98%
“…Our framework -suitably extended -could thus identify new performance bounds in each of these settings. Note added.-During the completion of our manuscript, we became aware of an independent work by Wang et al [62], which showed a result related to our Theorem 5 on the exponential scaling of required samples in variational algorithms.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, we study spatially local circuits of depth d on n qubits with Haar-random gates and local Pauli noise. The precise rate of convergence to the identity is a question of much significance in the complexity of random circuit sampling [GD18; BFLL21], the theory of benchmarking noisy circuits [ABIN96; Aha00; EAZ05; Boi+18; BSN17; Liu+21], and the investigation of near-term algorithms [SG21;Wan+21b;Wan+21a]. We prove upper and lower bounds on the expected total variation distance δ of the output distribution (when measuring in the computational basis) to the uniform distribution, which take the form δ ∼ exp − Θ(d) * .…”
Section: Introductionmentioning
confidence: 99%
“…An important question we leave open for future work is the extent to which noise affects the performance of our algorithm, and the degree to which error mitigation techniques [14], [43]- [47] can reduce the effects of the noise. Such an endeavor should take into consideration some recent theoretical and numerical work that have highlighted some limitations of quantum error mitigation on expectation estimation and training quantum circuits [48], [49].…”
Section: Discussionmentioning
confidence: 99%